Dampak kebijakan pengalihan dana Desa terhadap perekonomian masyarakat Desa Malaka Kabupaten Lombok Utara akibat Covid-19 - Fatia Rahmanita; Wirawan Jamhuri Wirawan Jamhuri (Jurnal Participative: Jurnal Pengabdian Pada Masyarakat, 2021)
Covid-19 is a disease caused by the Corona virus that emerged at the end of 2019 in Wuhan, China and has spread so rapidly almost troughout the world that is status was declared as Pandemic Covid-19 by the world health agency (WHO) on March 11, 2020. This virus is not only infecting health but also causes various crises in various sectors of community life, especially in the economic field. Therefore, Malaka Village, Pemenang Subdistrict, Nort Lombok Regency, which incidentally is a tourism area visited by many foreign tourist, experienced a drastic decline in the economy caused by the Covid-19 virus. Various efforts were made by the Village Government to cope with the impact of Covid-19, one of them was by diverting village funds. Initially to be allocated for the construction of infrastructure damage by the 2018 earthquake as an aid funds to support the local community’s economy.